Political determinants of municipal accounts: Quasi-experimental evidence from Portugal - Mariana Lopes da Fonseca (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2017)
This study investigates the impact of electing a majority in a municipality's legislative body on different items of the local current and capital accounts. Inference is based on a RDD approach and a dataset containing electoral and financial information for a sample of 278 homogeneous municipalities over 32 years. Results provide evidence of a significant causal impact of treatment on the most relevant items of the current and capital revenue and expenditure accounts. In particular, municipalities ruled by a legislative majority raise more revenues through current and capital transfers, but also have higher expenditures with personnel and investment goods.
Older version: http://hdl.handle.net/10419/109038
Keywords: 330; public finance; absolute majority